DESIGNING AN INTERNET OF THINGS (IoT)-BASED SMART IRRIGATION SYSTEM FOR KAMPUNGANYAR VILLAGE, BANYUWANGI - Tsalis Rahmad Darmawan; Jauhari Achmad; Wahyu Setiawan; Alfi Kurinita Widianti; Natasya Ika Marshanda; Priza Pandunata (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2026)
This study was conducted to design and implement an Internet of Things (IoT)-based smart irrigation system in mustard cultivation to improve water and energy efficiency and horticultural crop yields. The developed system combines soil moisture and temperature sensors connected to a microcontroller and an Android application to facilitate automatic and real-time irrigation monitoring and control. Trials were conducted on a 10 m × 4 m plot divided into 8 soil plots, using 80 sprayers and 32 drip irrigation points. The system is equipped with a 175-watt water pump with a flow rate of 70 liters per minute, which ensures even water distribution with a working pressure between 1.5 and 3.0 bar. The results of the study show that the use of an IoT-based irrigation system can increase water efficiency by up to 40% compared to manual methods and improve the growth parameters of mustard plants: plant height increased by 36.6%, the number of leaves increased by 42.7%, leaf width increased by 44.0%, and fresh weight increased by 48.1%. This system also reduces farmers' workload as watering is managed remotely via an application. Energy efficiency is achieved with an average consumption of 4.2 kWh per day (87% of the pump capacity), and the system demonstrates a high level of reliability with 97.2% availability during the testing period. The results of this study indicate that the application of IoT in precision irrigation systems not only improves resource use efficiency but also strengthens the development of sustainable and digital-based smart agriculture. This system has the potential to be applied to various other horticultural commodities to support increased productivity and efficiency in modern agriculture in Indonesia.